2018
DOI: 10.1016/j.watres.2018.03.056
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of endocrine activity in drinking water, surface water and treated wastewater from six countries

Abstract: The aquatic environment can contain numerous micropollutants and there are concerns about endocrine activity in environmental waters and the potential impacts on human and ecosystem health. In this study a complementary chemical analysis and in vitro bioassay approach was applied to evaluate endocrine activity in treated wastewater, surface water and drinking water samples from six countries (Germany, Australia, France, South Africa, the Netherlands and Spain). The bioassay test battery included assays indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(60 citation statements)
references
References 32 publications
3
56
1
Order By: Relevance
“…In addition, pathogenic bacteria such as Vibrio cholerae, Aeromonas hydrophila, Shigella, Plesiomonas shigelloides, and Salmonella species were isolated from the various river water sources in RSA [64]. This could be due to land runoff from areas characterized by the presence of grazing animals where manure may be applied on the soil, and where untreated rural and zootechnical wastewater may be directly released in the water bodies or spread on the soil, thus contributing to the emission of microorganisms in the rural water cycle [65]. investigated species ( Figure 5).…”
Section: Group South Africa Mozambiquementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, pathogenic bacteria such as Vibrio cholerae, Aeromonas hydrophila, Shigella, Plesiomonas shigelloides, and Salmonella species were isolated from the various river water sources in RSA [64]. This could be due to land runoff from areas characterized by the presence of grazing animals where manure may be applied on the soil, and where untreated rural and zootechnical wastewater may be directly released in the water bodies or spread on the soil, thus contributing to the emission of microorganisms in the rural water cycle [65]. investigated species ( Figure 5).…”
Section: Group South Africa Mozambiquementioning
confidence: 99%
“…In addition, pathogenic bacteria such as Vibrio cholerae, Aeromonas hydrophila, Shigella, Plesiomonas shigelloides, and Salmonella species were isolated from the various river water sources in RSA [64]. This could be due to land runoff from areas characterized by the presence of grazing animals where manure may be applied on the soil, and where untreated rural and zootechnical wastewater may be directly released in the water bodies or spread on the soil, thus contributing to the emission of microorganisms in the rural water cycle [65]. Matlou et al [66] found that in 170 water samples collected from springs, dams, and rivers in the North West province of South Africa, 45 samples were positive for the presence of the three species of Enterococcus: E. faecium, E. faecalis, and E. saccharolyticus frequently associated with vancomycin resistance determinants, usually responsible for in-hospital and community-acquired infections in humans.…”
Section: Group South Africa Mozambiquementioning
confidence: 99%
“…Median surface water estrogenicity was 1.8 ng/L and a maximum of 6.9 ng/L E2Eq BLYES was observed. Recently an EBT range of 0.1-0.5 ng/L E2Eq has been proposed [44]. Based on this EBT range, all the samples in the current dataset with quantifiable estrogenicity (90%) are within this trigger-level range.…”
Section: Discussionmentioning
confidence: 99%
“…Although tremendous progress has been achieved in adapting and validating in vitro tools to environmental monitoring and risk assessment (e.g., in Australasia, Coleman et al 2008;Mispagel et al 2009;Chinathamby et al 2013;Bain et al 2014;Escher et al 2014;Leusch et al 2014;Scott et al 2014;Roberts et al 2015;Boehler et al 2017;Neale, Achard et al 2017;Neale, Altenburger et al 2017;Chen et al 2018;Leusch et al 2018), some fundamental questions still need to be systematically addressed before these techniques can become reliable predictors of whole animal level effects: 1) Refine quantitative in vitro to in vivo extrapolation (QI-VIVE): Although there is a clear correlation between in vitro response and in vivo effects for some endpoints such as acute toxicity (Kaiser 1998;Tanneberger et al 2013;Natsch et al 2018) and receptor-mediated endocrine effects (Sonneveld et al 2006(Sonneveld et al , 2011Henneberg et al 2014), toxicokinetic factors (absorption, distribution, metabolism, and excretion) still pose a difficult challenge for QIVIVE (Blaauboer 2015;Meek and Lipscomb 2015), although groundbreaking studies suggest that this may soon be within reach (Rotroff et al 2010;Wetmore 2015). 2) Fully map relevant AOPs: There is still much work to be done to map key events (KEs) to connect the dots between the molecular or cellular initiating event and the ultimate apical consequence to produce comprehensive AOPs, for both humans and ecosystems ).…”
Section: Tools For Improving Risk Assessmentmentioning
confidence: 99%